Aplicação da flotação por ar dissolvido como pós-tratamento de efluente de lodo ativado em uma indústria de papel e celulose - Quartaroli, Larissa (2012)
The main objective of this work was to evaluate the performance of the dissolved air flotation in the post-treatment of effluents the activated sludge in a pulp and paper industry. The tests varying dosage of coagulant and polymer (anionic polymer and cationic polymer) were performed on a laboratory scale, using the equipment flotatest. In all the tests were fixed the values of rapid mix (500 s?¹), the rapid mix time (60 s), saturation pressure (5 bar) and the time of air saturation in the saturation chamber (15 mim), the other parameters were investigated and adopted during the research. The tests were divided in three steps: The objective of step 1 was to evaluate the response of the flotation system without the use of polymers and only coagulant (stage 1), with the use of anionic polymer (stage 2) and cationic polymer (stage 3). In step 2 were performed tests of crossflow microfiltration and analysis of the permeate flux with the effluent of the best configuration of flotation. In step 3, we assessed the removal of lignin and halogenic organic compounds of the best flotation results. The results indicated that the flotation with cationic polymer improved the effluent characteristics, with reduction up to 90% of turbidity, 85% of apparent color, 88% of true color and 68% of COD, using PAC coagulant dosage of 175 mg.L?¹ and 50 mg.L?¹ of cationic polymer, with flotation velocity of 9.0 cm/mim, excellent results for the reducing of the fouling of microfiltration membranes. The tests of lignin and halogenic organic compounds showed removal of more than 65% of these parameters. The flotation presented great potential for application in post-treatment of effluent from pulp and paper industry and effluent pre-treatment for microfiltration membrane.